Case Report: A man with septic shock developed convulsions - Linxiang Huang; Peiliang Gao; Xueying Fu; Yuran Wang; Jihong Zhu; Guiying Dong (Frontiers in Medicine)
Embolism has variable manifestations in infective endocarditis (IE) and might be misinterpreted in clinical settings. In this study, we reported the case of a 67-year-old man with erysipelas and septic shock who had developed a new onset of blurred vision and subsequently convulsions and multiple cerebral infarctions. Valve vegetations and patent foramen ovale were negative on the first echocardiography. After the neurologic symptom occurred, repeated echocardiography was performed and revealed vegetations on the mitral valve. As the patient had immunological complications, we suggested prolonged antibiotic therapy, but the patient requested an early discharge due to financial concerns. Under such circumstances, administering a long-acting penicillin G via an intramuscular injection once was an alternative therapy before discharge. For patients with bloodstream infection who develop any new onset symptoms related to arterial occlusion, infective endocarditis should be suspected, and repeated echocardiography is necessary.